Study on the Characteristics of a Composite Power System with a Tip-Jet-Driven Rotor - Yifei Wu; Yun Wang; Jinwu Wu; Jianxiang Tang (Aerospace)
Tip-jet helicopters operate by utilizing the reaction force generated by a high-speed tip jet, offering advantages such as a simplified and compact fuselage design and a reduction in empty weight by eliminating anti-torque balancing equipment. In tip-jet helicopter research, the composite power system is regarded as a crucial and bottleneck element. This study employs numerical simulations to comprehensively analyze the internal flow characteristics of the gas generator and tip-jet-driven rotor within the composite power system. Specifically, an in-depth investigation has been conducted on the influence laws of various parameters on the system characteristics. These parameters encompass the tip-jet-driven rotor speed, which takes on values of 50 rad/s, 80 rad/s, 100 rad/s, 120 rad/s, and 150 rad/s, the tip-jet-driven rotor length, measured at 1585 mm, 1785 mm, 1985 mm, 2185 mm, 2385 mm, 2585 mm, and 2785 mm, and the tip-jet-driven rotor nozzle area, which is specified by six values corresponding to multiples of the straight section area of the rotor’s internal channel, namely 0.25 times, 0.5 times, 0.75 times, 1 times, 1.25 times, and 1.5 times. The analysis of the obtained results indicates several significant relationships. Firstly, it is observed that the available moment exhibits a linear decrease as the tip-jet-driven rotor speed increases. Secondly, the maximum available moment is attained when the tip-jet-driven rotor length (L) satisfies the relationship L = Vr/2ω. Additionally, the maximum available power is achieved when the transport velocity of the tip-jet-driven rotor nozzle is precisely half of the relative velocity of the nozzle. Moreover, under the condition that the mass flow rate of the tip-jet-driven rotor nozzle remains constant, a positive correlation between the available moment and the reduction in the tip-jet-driven rotor nozzle area is noted.